Description of the male generative structures in Canna indica L. (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Dynamics of the mail generative structures development in Canna indica L. and its 4 cultivars is elucidated. Specific traits of the structures are shown and discussed.
Keywords: Canna indica, microsporangium, pollen grains.